Методологія культурології: методологічний плюралізм та міждисциплінарність - Уварова, Т.І. (Культура народов Причерноморья, 2013)
Стаття присвячена методологічній проблематиці культурології. В ній аналізуються та
узагальнюються основні підходи щодо культурологічного контексту методології; виділяються
міждисциплінарність та методологічний плюралізм як специфічний феномен методології культурології.
Декларується, що саме вони визначають специфіку методології культурології, сприяють розробці нових
методів і підходів,відкривають шляхи длярозумінняцілісностікультурних явищ. Статья посвящена методологической проблематике культурологии. В
статье анализируются и обобщаются основные подходы культурологического контекста методологии;
выделяются междисциплинарность и методологический плюрализм, как специфический феномен
методологии культурологии. Декларируется, что именно они определяют специфику методологи
культурологии, содействуют разработке новых методов и подходов, открывают пути
для понимания целостности культурных явлений. Cultural science is not an invariable science, it is a kind of scientific discipline that does not reach its
"theoretical maturity." Thus, cultural science as a young discipline requires clarification of some theoretical
positions. The aim of this article is to analyze and summarize the main approaches to the cultural context of
methodology, to distinguish interdisciplinarity and methodological pluralism as a specific cultural phenomenon
of the methodology of cultural science.
Proceed from the fact that general methodology studies the means and methods of obtaining a new knowledge,
as well as the bounds and possibilities of these methods, under the methodology of cultural science we mean the
systematic understanding of cultural phenomenas, cognitive methods and installations, which are grouped
around the concept “culture”.
In this article we define that the main problem of methodology is understanding of cultural science as a science.
On the one hand it is considered as a metascience, which synthesizes knowledge about the culture that has been
formed in other sphears, and thus has its own specifics and methodology. Opposite position is a total rejection of
cultural science as a science. The author follows the third point of view, adhering the position that cultural science can be regarded as an
interdisciplinary sphere that has common theory with the sciences, wish have knowledges about the various
aspects of culture.
In this article it was also declared that interdisciplinary researches in cultural science open the ways for
developing of new methods and approaches. A methodological pluralism is regarded as justified usage of
different methods,wich can be combined with each other on the basis of complementarity.
Interdisciplinarity and methodological pluralism determines the specific methodology of cultural science and
opens the ways of finding the lost integrity of the understanding of cultural phenomena.